2016
DOI: 10.3748/wjg.v22.i1.379
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans in liver cancer

Abstract: Proteoglycans are a group of molecules that contain at least one glycosaminoglycan chain, such as a heparan, dermatan, chondroitin, or keratan sulfate, covalently attached to the protein core. These molecules are categorized based on their structure, localization, and function, and can be found in the extracellular matrix, on the cell surface, and in the cytoplasm. Cell-surface heparan sulfate proteoglycans, such as syndecans, are the primary type present in healthy liver tissue. However, deterioration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 174 publications
1
79
0
5
Order By: Relevance
“…In KEGG analysis of mRNA and miRNA, the "proteoglycans in cancer" pathway is the most significant. Proteoglycans have been shown to play an important role in regulating cancer progression [55,57]. Furthermore, stemness can also be regulated by some proteoglycans [56,58].…”
Section: Discussionmentioning
confidence: 99%
“…In KEGG analysis of mRNA and miRNA, the "proteoglycans in cancer" pathway is the most significant. Proteoglycans have been shown to play an important role in regulating cancer progression [55,57]. Furthermore, stemness can also be regulated by some proteoglycans [56,58].…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate PG (HSPG) such as syndecans and glypicans are regulators of cancer progression and angiogenesis and serve as biomarkers for early detection and/or as pharmacological targets [116,117,118]. Notably, high concentrations of condroitin sulfate PG (CSPG), in particular versican and decorin, have been reported in the tumor stroma [111,119,120]. The major PGs affecting tumor angiogenesis are described below.…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…SRGN is constitutively secreted from the cells and integrated into the extracellular matrix [16]. Studies have shown that SRGN is mainly expressed in all normal hematopoietic cells [17], endothelial cells [18,19], tumor cells [20] and embryonic stem cells [21]. Moreover, serglycin plays an essential role in the formation of mast cell secretory granules and mediates the storage and secretion of various proteases, chemokines, and cytokines.…”
Section: Introductionmentioning
confidence: 99%